Cell-Taxi: Mesenchymal Cells Carry and Transport Clusters of Cancer Cells - Zarubova, Jana; Hasani-Sadrabadi, Mohammad Mahdi; Norris, Sam C P; Majedi, Fatemeh Sadat; Xiao, Crystal; Kasko, Andrea M; Li, Song (Small (Weinheim an der Bergstrasse, Germany), 2022)
Cell clusters that collectively migrate from primary tumors appear to be far more potent in forming distant metastases than single cancer cells. A better understanding of the collective cell migration phenomenon and the involvement of various cell types during this process is needed. Here, an in vitro platform based on inverted-pyramidal microwells to follow and quantify the collective migration of hundreds of tumor cell clusters at once is developed. These results indicate that mesenchymal stromal cells (MSCs) or cancer-associated fibroblasts (CAFs) in the heterotypic tumor cell clusters may facilitate metastatic dissemination by transporting low-motile cancer cells in a Rac-dependent manner and that extracellular vesicles secreted by mesenchymal cells only play a minor role in this process. Furthermore, in vivo studies show that cancer cell spheroids containing MSCs or CAFs have faster spreading rates. These findings highlight the active role of co-traveling stromal cells in the collective migration of tumor cell clusters and may help in developing better-targeted therapies.
Keywords: circulating tumor cell clusters; Neoplasms; mezenchymální kmenové buňky; micropatterned hydrogels; nádorové buněčné linie; Stromal Cells; Cell Movement; Humans; Mesenchymal Stem Cells; Cell Line, Tumor; collective cell migration; extracellular vesicles; pohyb buněk; nádory; spheroid migration assay; lidé; buňky stromatu